Students' evaluation of entrepreneurial university activities: A case from the Iran University of Medical Sciences. Issue 6 (December 2020) - Sanadgol, Siyamak; Dadfar, Mahboubeh
Among the key strategies in higher education is to prioritize the development of the entrepreneurial university. An appropriate entrepreneurship ecosystem in universities promotes higher education–industry relationships. Third-generation (innovative and entrepreneurial) universities and other higher education institutions depend on creativity, innovation, discovery and novelty. The aims of the present study were (a) to investigate the attitudes of Iranian students towards entrepreneurial university activities; (b) to investigate the psychometric properties of the Entrepreneurial University Activities Scale (EUAS); (c) to explore the factorial structure of the EUAS; and (d) to estimate gender-related differences. The EUAS was administered anonymously to 225 Iranian students. The mean of the EUAS total score was 43.44 (standard deviation = 26.61); Cronbach's α was 0.98. The indicator total correlations ranged from 0.82 to 0.95 (all significant at the 0.01 level). One component was extracted, labelled 'Entrepreneurial University Activities' (70.89% of the total variance). Gender-related differences were significant. Iranian students' evaluation of entrepreneurial university activities was negative, with entrepreneurial university indicators rated from none to very low. Iranian universities need to engage with industry and business. Knowledge-based companies should be supported. Technology parks, growth and accelerator centres should be equipped and updated. A sustainable financial strategy to support the development of creativity, innovation, technology, commercialization and entrepreneurship should be developed. Internationalization, as an important part of entrepreneurship strategy in a university, should be considered. The analytic hierarchy process network analysis technique is recommended for the evaluation of entrepreneurial university activities and the components influencing it.